Increased metal content in the TDP-43A315T transgenic mouse model of frontotemporal lobar degeneration and amyotrophic lateral sclerosis - Dang, Theresa; Lim, Nastasia; Grubman, Alexandra; Li, Qiao-Xin; Volitakis, Irene; White, Anthony R.; Crouch, Peter (Frontiers in Aging Neuroscience, 2014)
Disrupted metal homeostasis is a consistent feature of neurodegenerative disease in humans and is recapitulated in mouse models of Alzheimer’s disease, Parkinson’s disease, amyotrophic lateral sclerosis (ALS) and neuronal ceriod lipofuscinosis. While the definitive pathogenesis of neurodegenerative disease in humans remains to be fully elucidated, disease-like symptoms in the mouse models are all driven by the presence or over-expression of a putative pathogenic protein, indicating an in vivo relationship between expression of these proteins, disrupted metal homeostasis and the symptoms of neuronal failure. Recently it was established that mutant TAR DNA binding protein-43 (TDP-43) is associated with the development of frontotemporal lobar degeneration (FTLD) and ALS. Subsequent development of transgenic mice that express human TDP-43 carrying the disease-causing A315T mutation has provided new opportunity to study the underlying mechanisms of TDP-43-related neurodegenerative disease. We assessed the cognitive and locomotive phenotype of TDP-43A315T mice and their wild-type littermates and also assessed bulk metal content of brain and spinal cord tissues. Metal levels in the brain were not affected by the expression of mutant TDP-43, but Zn, Cu and Mn levels were all increased in the spinal cords of TDP-43A315T mice when compared to wild-type littermates. Performance of the TDP-43A315T mice in the Y-maze test for cognitive function was not significantly different to wild-type mice. By contrast, performance of the TDP-43A315T in the rotarod test for locomotive function was consistently worse than wild-type mice. These preliminary in vivo data are the first to show that expression of a disease-causing form of TDP-43 is sufficient to disrupt metal ion homeostasis in the central nervous system. Disrupted metal ion homeostasis in the spinal cord but not the brain may explain why the TDP-43A315T mice show symptoms of locomotive decline and not cognitive decline.